2021
DOI: 10.1021/acsomega.0c04770
|View full text |Cite
|
Sign up to set email alerts
|

Lab Case Study of Microbiologically Influenced Corrosion and Rietveld Quantitative Phase Analysis of X-ray Powder Diffraction Data of Deposits from a Refinery

Abstract: This paper reports a laboratory-based case study for the characterization of deposits from a crude cooler and reboilers in a Saudi Aramco refinery by microbiologically influenced corrosion (MIC) using microbial, metallurgic, and special analyses and correlates the Rietveld quantitative phase analysis of high-resolution X-ray powder diffraction (XRD) data of scale deposits with microbe compositions. Therefore, rapid in-field microbiological assays could be carried out to assess the potential of MIC. Based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Therefore, rapid in-field microbiological assays could be carried out to assess the potential of MIC. Based on the results, it can be highlighted that the MIC investigation showed that total bacteria and SRB were detected in all sampling locations [118].…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 93%
“…Therefore, rapid in-field microbiological assays could be carried out to assess the potential of MIC. Based on the results, it can be highlighted that the MIC investigation showed that total bacteria and SRB were detected in all sampling locations [118].…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 93%
“…Subsequently, high-resolution data were measured using the Rigaku ULTIMA-IV multi-purpose X-ray powder diffractometer, with a copper X-ray tube, scan range 5–50° 2θ, a step size of 0.04°, and a scan rate of 1° per minute. Moreover, all of the data sets were identified and quantified (i.e., crystallinity percentage) by High Score Plus software combined with the ICDD PDF-4+ database of the standard reference materials . Additionally, the details of the small-angle X-ray scattering are given by Ding et al…”
Section: Methodsmentioning
confidence: 99%
“…The pellet sample was irradiated with X-ray photons from the X-ray tube. The intensity of the X-rays was processed by the PANalytical instrument’s software (i.e., Omnian) to determine semiquantitatively the concentrations of the detected elements …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations